Mental Accounting and Business Decision-Making within SMEs: A Covid-19 Pandemic Phenomenon - Maria Entina Puspita; Bertha Kusuma Wardani (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
This study aims to analyze the mental accounting of SME actors in business decision-making in the midst of the Covid-19 pandemic. The objects of this study are the SMEs in Salatiga City. The data collection technique uses accidental sampling with the SME respondents who were willing to be interviewed during the research. The study employs a questionnaire from 100 respondents. This study is mixed-method research. The quantitative approach is to process the accounting information owned by SME actors in business decision-making and detect mental accounting when dealing with the COVID-19 pandemic. The qualitative approach is interviewing SME actors. The results show a mental accounting in terms of the separation of business finances and personal finances. Most SME actors allocate income to certain necessities. The recording of transactions has been done even though the records are limited to certain records. The income and costs incurred were separated for the business. The SMEs actors already have business decisions in the income cycle, expenditure cycle, production cycle, HR management cycle, and payroll and funding cycle decisions. In making these decisions, SME actors rely more on unwritten accounting information such as market price estimates, the estimated cost of goods sold, estimated production costs, owners' memories of the amount of inventory they have, as well as direct physical inspection of inventories to make good business decisions. The main contribution of this researchdemonstrates that the Covid-19 pandemic has shaped new behavior relating to business decision-making by the separation of business and personal finances.